Internal Conflict among Single Parents in the Divorce Decision Making Process: A Case Study of Three Single Mothers - Revinda Adelia Savitri; Rona Ghina Luqyana; Fara Artika Setiawan; Muhammad Rendy Eka Saputra; Della Puteri Anggraeni (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to explore the intrapsychic conflicts experienced by three female single parents during the process of divorce decision-making through the lens of Freud's psychoanalytic theory within the context of family psychology. The study employed a qualitative approach using a multiple case study design. The participants consisted of three divorced women who were single parents, selected through purposive sampling. Data were collected through semi-structured in-depth interviews with each participant and analyzed using thematic analysis based on Freud's psychoanalytic framework of the Id, Ego, and Superego. The findings across the three cases indicate that intrapsychic conflict emerged as a manifestation of the dynamic tension between the Id, which drives the desire to escape emotional suffering; the Superego, which imposes moral constraints rooted in religious and family values; and the Ego, which mediates these opposing forces through defense mechanisms such as repression and rationalization. Although the participants came from different personal and family backgrounds, they exhibited similar psychological dynamics in negotiating emotional distress, moral obligations, and the decision to end their marriages. These findings highlight the relevance of Freud's psychoanalytic perspective in understanding the psychological complexities underlying divorce decision-making among female single parents and provide valuable insights for family counseling and psychological intervention.